REFORMASI KURIKULUM PENDIDIKAN ISLAM DI PERGURUAN TINGGI ISLAM INDONESIA PADA ABAD KE-20 - Nida Wahyu Sa’bani; Qurrotu Aini; Rizka Prihatiningsih (Al-SAMBASY: Jurnal Kajian Pendidikan, 2026)
Islamic education in Indonesia has undergone a long journey in reforming its curriculum to remain relevant to the demands of the modern era. This study aims to examine the curriculum reform of Islamic higher education in Indonesia during the 20th century, encompassing its background, forms and processes of change, and its overall impact on Islamic education. A qualitative approach was employed using library research method through analysis of relevant written sources. The findings reveal that curriculum reform was driven by both internal and external factors, including dissatisfaction with the traditional and dichotomous education system, the influence of reformist Islamic thought from the Middle East, and pressures of modernization and globalization. The reform process unfolded gradually, characterized by a structural shift from a monodisciplinary curriculum toward integrated models of knowledge, culminating in the transformation of IAIN into State Islamic Universities (UIN). Various integration models were developed, including the Integration-Interconnection concept by Amin Abdullah, Wahdatul Ulum by UIN North Sumatra, and Unity of Sciences by UIN Walisongo. Pedagogical renewal accompanied the curricular changes, marked by a shift from teacher-centered to student-centered learning approaches. Key figures such as Harun Nasution and Azyumardi Azra, supported by national and international institutions, played decisive roles in driving these reforms. Curriculum reform has demonstrably improved graduate quality and broadened the orientation of Islamic education, although implementation challenges such as infrastructure disparities and resistance to change continue to require sustained attention.